Directional vs non-directional modes of vibrotactile feedback for arm posture replication - Causo, Albert (2013)
This paper presents an integrated system for upper limb rehabilitation which uses small inertia-based sensors and vibrotactile feedback devices. Vibrotactile feedback is incorporated together with two Inertial Measurement Units (IMUs) attached at the upper arm and the forearm to measure arm motions. The whole arm posture is modeled using three parameters wrist position, elbow position, and forearm's orientation. Two different strategies of utilizing vibrotactile feedback for arm posture replication are discussed in this paper. The vibrotactile feedback is used firstly as a directional indicator and secondly as a non-directional indicator that informs the user of matching errors between the current posture and the target posture. The experiments involve seven student volunteers replicating five different arm postures. Results show that the non-directional vibrotactile feedback enables faster and more accurate arm posture correction.